(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The current study aimed to evaluate the level of IL12 CYTOKINE and how it correlates with the level of lipids in diabetic patients. The results indicated a mean elevation in IL-12 levels among the research participants (11.85: SE 0.64) compared to the control group (6.63: SE 0.34). This cytokine may be critical in the development of T2DM, in which inflammatory reactions associated with IL-12 gene expression are accelerated by interfering with excessive insulin concentration. It also showed an insignificant correlation between this cytokine and lipid levels.